(untitled) (Triwikrama: Jurnal Ilmu Sosial, 2025)
This article aims to examine Indonesian society’s understanding of LGBT by analyzing public opinion dynamics in the context of social change. Through a literature review of eight scholarly sources, it was found that the social construction of LGBT is largely influenced by religious and cultural conservatism. Negative perceptions are often reinforced by narrow religious interpretations and biased media representation, leading to stigma and discrimination. However, amid globalization, there are signs of shifting perceptions, especially among younger generations. Social adaptation by LGBT communities also reveals the potential for acceptance through participatory interaction. This study highlights the importance of human rights-based and intercultural dialogue approaches in promoting a more just public understanding of sexual identity diversity.